Ultrastructural modifications in Common ash tissues colonised by Chalara fraxinea - DAL MASO, Elisa; FANCHIN, Genny; MUTTO ACCORDI, Sergio; SCATTOLIN, Linda; MONTECCHIO, Lucio (Phytopathologia Mediterranea, 2012)
Chalara fraxinea, the cause of ash dieback, is present in many European countries and constitutes a severe threat to Fraxinus spp. in forests, urban areas and nurseries. This study investigated tissue colonisation strategies of the parasite in Common ash at ultrastructural level and demonstrated that C. fraxinea develops intracellularly, moving through the cells and easily colonising the phloem, paratracheal parenchyma and parenchymatic rays. However, damage to either the plasmalemma or cell walls was not observed under our experimental conditions. Furthermore, the presence of intrahyphal hyphae was frequently detected, which are likely associated with a regeneration mechanism.